DNA damage and repair: underlying mechanisms leading to microcephaly - Ribeiro, Jessica Honorato; Altinisik, Nazlican; Rajan, Nicholas; Verslegers, Mieke; Baatout, Sarah; Gopalakrishnan, Jay; Quintens, Roel (Frontiers in Cell and Developmental Biology, 2023)
DNA-damaging agents and endogenous DNA damage constantly harm genome integrity. Under genotoxic stress conditions, the DNA damage response (DDR) machinery is crucial in repairing lesions and preventing mutations in the basic structure of the DNA. Different repair pathways are implicated in the resolution of such lesions. For instance, the non-homologous DNA end joining and homologous recombination pathways are central cellular mechanisms by which eukaryotic cells maintain genome integrity. However, defects in these pathways are often associated with neurological disorders, indicating the pivotal role of DDR in normal brain development. Moreover, the brain is the most sensitive organ affected by DNA-damaging agents compared to other tissues during the prenatal period. The accumulation of lesions is believed to induce cell death, reduce proliferation and premature differentiation of neural stem and progenitor cells, and reduce brain size (microcephaly). Microcephaly is mainly caused by genetic mutations, especially genes encoding proteins involved in centrosomes and DNA repair pathways. However, it can also be induced by exposure to ionizing radiation and intrauterine infections such as the Zika virus. This review explains mammalian cortical development and the major DNA repair pathways that may lead to microcephaly when impaired. Next, we discuss the mechanisms and possible exposures leading to DNA damage and p53 hyperactivation culminating in microcephaly.